An application of inverse Pad´e interpolation - TRÂMBIȚAȘ, Radu T. (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
We use inverse Pad´e interpolation to find a fourth order method for the solution of scalar nonlinear equations. Our approach is based on Computer Algebra. Maple Computer Algebra system assisted us to find the method and to establish its order. Mathematics Subject Classification (2010): 65H05, 65Y99.